Do invisível ao visível: em busca de imagens da lesbianidade - Adriana Agostini de Resende (2015)
This thesis intends to verify how the inter-text among lesbianism images occurs from analyzing the TV series The L Word. One can assume that the program uses a set of images esthetic representation and narrative fragments that compound that lesboland, that means, an archipelago of images from the past and the present and also future expectations in which different homosexual ladies live. Based on the concept of space and experience developed by Reinhart Koselleck and Paul Ricouer, it intends to understand how the lesboland shows itself by a dialogical tension among its images. In other words, how these images can connect each other and can be considered part of the lesbian traditions, fictionally speaking. In order to achieve it, three lesbian characters from the TV series have been chosen, and their convening, tensioning, re-setting and refreshing the lesbianism images were caught.